Care of the postpartum patient after premature rupture of membranes - Morales-Amao, Maruja; Morales-Romaní, Yaquilina; Cabanillas-Chavez, María Teresa; Morales Garcia, Wilter C. (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introduction: According to the World Health Organization, premature rupture of membranes (PROM) represents between 8 and 10% of pregnancies, being common the conclusion of the same in a cesarean section, through which the fetus is extracted through the abdominal route, this can generate complications such as acute postoperative pain in the incision area. Objective: To expose the nursing care in a post-cesarean patient due to PROM. Methodology: Qualitative clinical case research, represented by a 31-year-old patient selected for convenience. The assessment method is the nursing care process and the data collection instrument is constituted by the 11 patterns of Marjory Gordon. Results: Eight nursing diagnoses were identified, of which acute pain R/C, physical injurious agent (surgical procedure) secondary to severe oligohydramnios and/or operative wound, gesture of pain, VAS 8 was selected as the main one. From the main diagnosis, nursing interventions were proposed taking into account the NOC and NIC taxonomy. Likewise, the main CR, uterine atony, still has no clear results, since the risk will continue in the following hours. Conclusions: Nursing care had a favorable effect on altered functional patterns, achieving an optimal score according to the NANDA, NIC and NOC taxonomy. However, the patient remains hospitalized to continue providing nursing care, favoring the recovery of her health. However, the outcome of the interventions in the main CR remains to be determined.